NONTRADITIONAL APPROACHES TO DENTAL ANAESTHESIA ADMINISTRATION - Xudoykulov Shaxzod Shavkatovich (The Conference Hub, 2025)
The administration of local anaesthesia is an indispensable element of the provision of exceptional dental care. Contemporary dentistry's most frequently employed pain relief technique is the administration of an anaesthetic. However, the anxiety and dread that arise both before and during the injection continue to pose a challenge for a significant number of children and adults who are engaging in dental treatment. Additionally, complications related to injections persist. The development of new pain relief methods and devices has allowed physicians to maintain a higher level of professionalism in their work and provide high-quality dental care.
Keywords: local anaesthesia, electronic dental anaesthesia, computer-controlled local anaesthesia, and needle-free injector.